AN ANALYSIS OF SLANG IN NICKI MINAJ’S RAP SONGS “SEEING GREEN” AND “FRACTIONS”: A SOCIOLINGUISTIC STUDY - Marlin Taba Leko; Tri Septa Nurhantoro; Yohanes Angie Kristiawan (Universitas Respati Yogyakarta (UNRIYO), 2023)
This research analyzes the slang word types used by Nicki Minaj in her songs “Seeing Green” and